Eclipse of the Sunnis power, exile, and upheaval in the Middle East - Amos, Deborah (PublicAffairs, 2010)
The Middle East is experiencing Post-Traumatic Shock-and-Awe Disorder, roiled by the unintended after-effects of the removal of a geopolitical cornerstone: Saddam Hussein's Sunni-dominated Iraq. Four million Iraqis were displaced by the conflict; two million of them left the country. Iraq's demographic balance shifted and it became a Shiite-dominated state. Jordan's Sunnis found themselves isolated and without a strong regional ally, and Lebanon's Sunnis faced an internal challenge from Hezbollah's Shiites, emboldened by the new power shift in Iraq. The rise of Iranian-backed Shiite parties and militias was predicted; the consequences of the Sunni eclipse almost entirely overlooked. Yet it is this newly displaced population that is likely to determine the future complexion of the region. Deborah Amos is a distinguished and expert reporter. In Eclipse of the Sunnis she gives voice to the experience of exile and the ongoing trauma of the dispossessed and displaced. She shows how individual stories have combined to create a new political dynamic in the Middle East that, no matter that it is of our making, we have almost no idea how to manage or control.